Pengaruh Current Ratio, Earning Per Share, Debt To Asset Ratio, dan Total Asset Turnover, Terhadap Harga Saham (Studi Empiris pada Perusahaan Sub Industri Perkebunan dan Tanaman Pangan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2022) - Alikah Eka Disti; Mia Laksmiwati (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to determine the effect of Current Ratio, Earning Per Share, Debt to Asset Ratio, and Total Asset Turnover on Stock Price. This study uses secondary data. The population in this study was 25 companies in the Plantation and Food Crops Sub-Industry listed on the Indonesia Stock Exchange for the period 2017-2022. The sampling technique used was purposive sampling method and obtained a sample of 16 companies. The analysis technique used is multiple linear regression analysis test using the Statistical Program for Social Science (SPSS) version 22 program. The results of this study indicate that Earning Per Share have a positive and significant effect on Stock Price, while Current Ratio, Debt to Asset Ratio, and Total Asset Turnover have no effect on Stock Price.